Strategies to Improve Running Economy in Trained Distance Runners - Barnes, Kyle (Auckland University of Technology, 2014)
Running economy is considered an important physiological measure for endurance athletes, especially distance runners. Of the numerous metabolic, cardiopulmonary, biomechanical and neuromuscular characteristics contributing to running economy, it seems that few are subject to alteration or improvement through training or other interventions. Over the past decade, various strategies to improve running economy have been investigated, but the evidence supporting different forms of movement-specific resistance exercises is limited and conflicting. Furthermore, there is a paucity of data evaluating the subsequent effects of changes in running economy on actual running performance. Given a range of mechanisms have been described as meditators to explain changes in running economy (Chapter 2) following various training strategies (Chapter 3) the initial aim of this thesis was to describe the determinants of running economy in a population analogous to that of which would participate in the ensuing experimental studies (Chapter 4). To determine factors and to assess the efficacy of different movement-specific resistance strategies to improve running economy and running performance, one descriptive and three experimental studies were conducted with a variety of methodological approaches to address the main aim of this thesis: to examine the relative efficacy of different forms of movement-specific resistance exercise to improve running economy and performance in competitive distance runners. The purpose of Chapter 4 was to evaluate the lower-body determinants of running economy among well-trained male and female distance runners. Leg stiffness (r = -0.80) and Achilles moment arm length (r = 0.90) had high to extremely high correlations with running economy and each other (r = -0.82), whereas correlations between running economy and kinetic measures (peak force, peak power and time to peak force) for both genders were unclear and biomechanical measures (stride rate, stride length, contact time, flight time) were small-moderate. At all common test velocities women were more economical than men (effect size (ES) = 0.40). The results of Chapter 4 suggested that while lower-body stiffness and Achilles moment-arm length were substantially related to the running economy of well-trained runners, no single lower-body measure could fully explain differences in running economy between individuals or genders. Running economy is therefore likely determined from the sum of influences from multiple lower-body attributes. The purpose of Chapter 5 was to determine the acute effects of wearing a weighted vest during warm-up "strides" on running economy, neuromuscular measures, and running performance. The weighted-vest condition resulted in a 6.0% improvement in running economy along with a 20% increase in leg stiffness, which resulted in a 2.9% enhancement in peak running speed. Relationships between change scores showed that changes in leg stiffness could explain all the improvements in performance and running economy. Results from study two showed that running economy and performance could be improved following a movement-specific form of resistance exercise. Another common way runners obtain resistance to movement is various forms of uphill running. Consequently, Chapter 6 examined the optimum loading parameters to five different uphill interval-training programs. There was no clear optimum for time-trial performance, and the mean improvement across each training intensity was ~2.0%, however, the highest intensity was clearly optimal for running economy (improvement of 2.4%), and for all neuromuscular measures, whereas other aerobic measures were optimal near the middle intensities. These findings supported anecdotal reports for incorporating uphill interval training in the training programs of distance runners to improve running economy and other physiological parameters relevant to running performance. The final part of this thesis focused on two forms of resistance training (heavy-resistance training and plyometric training), which each offer distinct physiological and neuromuscular adaptations that previously have been shown to enhance running economy on their own. Therefore the last experimental study (Chapter 7) examined the effects of combining these two modes of resistance training on running economy and competition performance in male and female cross-country runners. Results showed that heavy-resistance training produced small to moderate improvements in peak speed (male 3.4%, female 2.2%), running economy (male 1.5%, female 2.5%) and neuromuscular characteristics relative to plyometric resistance training, whereas changes in biomechanical measures favored plyometric resistance training. Overall, males made less absolute gains than females in most tests. Both treatments had possibly harmful effects on competition times in males (0.5% ±1.2%), but there may have been benefit for some individuals, whereas both treatments were likely beneficial for all females (-1.2%; ±1.3%), but heavy-resistance was possibly better than plyometric resistance training. Overall, the findings from this thesis have demonstrated for the first time that well-trained distance runners can substantially (2 to 6%) improve their running economy through acute and chronic bouts of movement-specific resistance exercise, either by performing strides with a weighted vest or short-duration near-maximal uphill sprints. Furthermore, it appears that heavy resistance-training is a superior training modality to the combination of heavy-resistance and plyometric training at enhancing running economy. Regardless of the exercise mode, improvements in running economy appear to be modulated through enhancements in lower-body stiffness, but other trainable and non-trainable factors may be related to and affect running economy. Moreover, it appears that the improvements in running economy following various training strategies presented in the thesis contribute to improved running performance.
Keywords: Running economy; Running performance